Normal human macula densa morphology and cell turnover: A histological, ultrastructural, and immunohistochemical investigation. Issue 11 (28th June 2020) - Lorenzi, Teresa; Graciotti, Laura; Sagrati, Andrea; Reguzzoni, Marcella; Protasoni, Marina; Minardi, Daniele; Milanese, Giulio; Cremona, Ottavio; Fabri, Mara; Morroni, Manrico
Abstract: The aim was to analyze the morphology of normal human macula densa (MD), evaluate the cells that may be responsible for its turnover, and collect quantitative data. Of four samples of normal human renal tissue, two were embedded in resin to measure the longitudinal extension and examine the ultrastructure of the MD, the other two were embedded in paraffin to study apoptosis and cell proliferation. The MD is composed of a monolayer tissue about 40 μm long, which includes 35–40 cells arranged in overlapping rows. Ultrastructurally, MD cells show two polarized portions: an apical end, with sensory features, and a basolateral aspect, with paracrine function. MD cells are connected apically by tight junctions, with/without adherens junctions, which form a barrier between the distal tubule lumen and the interstitium. Cells in degeneration, often associated with macrophages, and undifferentiated cells were found in the MD and adjacent distal tubule. A filamentous mat previously described in proximal tubule scattered tubular cells (STCs) was detected in the basal cytoplasm in undifferentiated cells. The tissue was consistently negative for the proliferation marker Ki67 and for the apoptotic markers caspase‐3 and caspase‐9. This work confirms our earlier morphological findings and provides new data: (a) MD cells display both apical adherens and tight junctions, the latter forming a tubulo‐mesangial barrier; (b) the MD is a monolayer made up of about 40 cells arranged in rows; (c) the simultaneous presence of degenerating (8–13%) and undifferentiated (4–13%) cells reminiscent of STCs suggests a non‐negligible cell turnover.